please help fast fast
Attachments:
![](https://hi-static.z-dn.net/files/d72/bb47cda39cbec2d1af1c725c7dc57d91.jpg)
Answers
Answered by
0
Answer:
(-3)³ × (-3)⁴ = [(-3) × (-3) × (-3)] × [(-3) × (-3) × (-3) × (-3)]
= (-3)3+4
= (-3)⁷
4. m⁵ × m³ = (m × m × m × m × m) × (m × m × m)
= m5+3
= m⁸
From the above examples, we can generalize that during multiplication when the bases are same then the exponents are added.
Similar questions
Math,
1 month ago
Math,
1 month ago
Math,
1 month ago
Social Sciences,
3 months ago
Chemistry,
3 months ago
Computer Science,
11 months ago